Intravascular catheter migration: A cross-sectional and health-economic comparison of adhesive and subcutaneous engineered stabilisation devices for intravascular device securement. Issue 1 (January 2020) - McParlan, Dympna; Edgar, L; Gault, M; Gillespie, S; Menelly, R; Reid, M
The Infusional Services Team at a large cancer centre in Belfast, Northern Ireland, performed a cross-sectional analysis of two catheter securement technologies to address an area of frequent, but underestimated concern – peripherally inserted central catheter migration and dislodgement. Healthcare practitioner and patient feedback, along with economic impact, were assessed. The costs associated with catheter replacement during the adhesive device group study period were calculated using an average cost per insertion, based on material costs required for the procedure. Other factors were the replacement cost of the adhesive engineered securement device with each dressing change. In the subcutaneous securement group, the material costs were adjusted for use of the subcutaneous device as it remained in situ for the duration of the catheters' dwell time. This review found that subcutaneous securement offers both patient and facilities a safe, effective and economical alternative for device securement with patients who are unable to tolerate or have successful securement with adhesive securement devices. The use of subcutaneous devices provided for reduced risks for peripherally inserted central catheters in terms of dislodgement, migration or malposition, alleviating the potential risks to develop catheter-related thrombosis and device-related infection.